Antecedents of Organic Rice Repurchase Intention in E-Commerce - Nahda Nazhirah; Elisabet Siahaan; Sri Fajar Ayu (Baileo: Jurnal Sosial Humaniora, 2026)
Growing public awareness of healthy lifestyles and environmental sustainability has contributed to the increasing consumption of organic rice in Indonesia. However, consumers’ repurchase intention through e-commerce platforms remains relatively unstable. This study aims to analyze the influence of attitude, subjective norms, perceived behavioral control, environmental concern, and health consciousness on consumers’ repurchase intention toward organic rice through e-commerce. This study employed a quantitative approach involving 100 respondents aged 30–55 years who had purchased organic rice through e-commerce at least twice in the past year. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that attitude, perceived behavioral control, environmental awareness, and Health Consciousness have a positive and significant effect on repurchase intention, whereas subjective norms do not have a significant effect. These findings suggest that repurchase intention is more influenced by internal factors than by external factors.